Os conceitos de representação e recursividade na obra do jovem Peirce - Amaral, Gustavo Rick (2014)
This thesis addresses the type of definition or characterisation used by Peirce to formulate a central concept within his semiotics: the concept of representation. Analyses carried out to support this thesis are limited to Peirce's texts from the end of the 1860s, an era in which Peirce's thinking begins to detach itself from his Kantian matrix and take on its own features. The focus of all research conducted in support of this thesis is the logical element of Charles S. Peirce s philosophical system, i.e. the argumentative structuring developed by the philosopher to validate the theories offered as responses to philosophical problems. Differently from dyadic approaches developed to explain the workings of a representation process, the conception of representation elaborated by Peirce within semiotics is triadic and such difference is far from merely numerical. Our thesis is that, with the introduction of this third element (the interpretant), characterisation of the concept of representation (elaborated within Peircean semiotics) becomes recursive by necessity and such characterisation is an in-built requirement of the theory that Peirce intends to offer as an answer to what he considered to be the central issue of philosophy: how is synthetic (i.e. ampliative) reasoning possible or, from another angle, how is it possible for knowledge to grow? With a view to proving our thesis in respect of the necessity for this type of conceptual characterisation within the Peircean philosophical project, we have dedicated a significant part of this text to the task of establishing not only that semiotics is central to such a project, but also to demonstrating that some central semiotic theses are a direct result of the fact that the concept of representation has been defined or characterised in a recursive manner. These central theses were termed elementary theses (of semiotics): "there is no first sign (in an interpretative process)" and there is no last sign (in an interpretative process)". Therefore, to render the theoretical solution found by Peirce sustainable for the (what he considered to be) central issue of philosophy, the two elementary theses referred to above must be established within semiotic theory (developed by Peirce himself), and their establishment depends on the recursion found within the concept of a sign or of a representative process (and introduced by the concept of interpretant). Our thesis is, therefore, precisely that the characterisation or definition of the concept of representation at the heart of the Peircean semiotics sign concept is necessarily recursive, because without such recursion it would simply be impossible to derive the two elementary theses of semiotics